Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's solve this system of linear equations step by step.
We are given the system of equations:
[tex]\[ \begin{cases} -7x - 2y = 14 \\ 6x + 6y = 18 \end{cases} \][/tex]
### Step 1: Simplify the Equations if Possible
First, we’ll simplify the second equation:
[tex]\[ 6x + 6y = 18 \][/tex]
Divide every term by 6:
[tex]\[ x + y = 3 \quad \text{(Equation 2)} \][/tex]
### Step 2: Use Substitution or Elimination
We can use the substitution method here. Express [tex]\(y\)[/tex] from Equation 2:
[tex]\[ y = 3 - x \quad \text{(Equation 3)} \][/tex]
### Step 3: Substitute into the First Equation
Now, substitute Equation 3 into the first equation:
[tex]\[ -7x - 2(3 - x) = 14 \][/tex]
Simplify this equation:
[tex]\[ -7x - 6 + 2x = 14 \][/tex]
Combine like terms:
[tex]\[ -5x - 6 = 14 \][/tex]
Add 6 to both sides:
[tex]\[ -5x = 20 \][/tex]
Divide both sides by -5:
[tex]\[ x = -4 \][/tex]
### Step 4: Substitute [tex]\(x\)[/tex] Back into Equation 3
Now, substitute [tex]\(x = -4\)[/tex] back into Equation 3:
[tex]\[ y = 3 - (-4) \][/tex]
Simplify:
[tex]\[ y = 3 + 4 \\ y = 7 \][/tex]
### Step 5: Write the Solution
Therefore, the solution to the system of equations is:
[tex]\[ x = -4 \][/tex]
[tex]\[ y = 7 \][/tex]
We can now fill in the blanks:
[tex]\[ x = -4 \][/tex]
[tex]\[ y = 7 \][/tex]
This means the solution to the system of equations is [tex]\((-4, 7)\)[/tex].
We are given the system of equations:
[tex]\[ \begin{cases} -7x - 2y = 14 \\ 6x + 6y = 18 \end{cases} \][/tex]
### Step 1: Simplify the Equations if Possible
First, we’ll simplify the second equation:
[tex]\[ 6x + 6y = 18 \][/tex]
Divide every term by 6:
[tex]\[ x + y = 3 \quad \text{(Equation 2)} \][/tex]
### Step 2: Use Substitution or Elimination
We can use the substitution method here. Express [tex]\(y\)[/tex] from Equation 2:
[tex]\[ y = 3 - x \quad \text{(Equation 3)} \][/tex]
### Step 3: Substitute into the First Equation
Now, substitute Equation 3 into the first equation:
[tex]\[ -7x - 2(3 - x) = 14 \][/tex]
Simplify this equation:
[tex]\[ -7x - 6 + 2x = 14 \][/tex]
Combine like terms:
[tex]\[ -5x - 6 = 14 \][/tex]
Add 6 to both sides:
[tex]\[ -5x = 20 \][/tex]
Divide both sides by -5:
[tex]\[ x = -4 \][/tex]
### Step 4: Substitute [tex]\(x\)[/tex] Back into Equation 3
Now, substitute [tex]\(x = -4\)[/tex] back into Equation 3:
[tex]\[ y = 3 - (-4) \][/tex]
Simplify:
[tex]\[ y = 3 + 4 \\ y = 7 \][/tex]
### Step 5: Write the Solution
Therefore, the solution to the system of equations is:
[tex]\[ x = -4 \][/tex]
[tex]\[ y = 7 \][/tex]
We can now fill in the blanks:
[tex]\[ x = -4 \][/tex]
[tex]\[ y = 7 \][/tex]
This means the solution to the system of equations is [tex]\((-4, 7)\)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.